Effect of Quality Control Circle Activity Nursing Combined with Respiratory Function Exercise Nursing on Patients with Esophageal Cancer. (17th September 2022) - Yu, Hairu; Li, Sha; Shi, Shasha
Abstract : Objective . To explore the effect of quality control circle activity nursing combined with respiratory function exercise nursing on esophageal cancer patients' immune function and nutritional status. Methods . The clinical case data of 119 esophageal cancer patients admitted to our hospital were selected as the research objects from May 2019 to July 2021. They were divided into the quality control circle activity care group (QCCAC) (9 cases dropped due to incomplete case data, n= 50) and respiratory function exercise care group (10 cases dropped due to incomplete case data, n=50) by the random number table method, the respiratory function exercise care group was treated with respiratory function exercise care, while the QCCAC group was treated with QCCAC. Changes in lung function, immune function, and nutritional status before and after nursing were compared in the two groups of patients. Results . Before nursing, there was no significant difference in pulmonary function indexes, immune function indexes, and the level of nutritional status indicators between the two groups (P > 0.05 ). After nursing, the finger pulse oxygen saturation, vital capacity (VC), respiratory rate, forced vital capacity (FVC), deep inspiratory volume (IC), and maximum ventilation (MVV) of the QCCAC improved, and the QCCAC group was significantly higher than the respiratory function exercise care group (P < 0.05 ). After nursing, the QCCAC's CD3+, CD4+, IgG, IgM, and IgA levels increased, and the QCCAC group was significantly higher than the respiratory function exercise care group. The CD8+ level decreased, and the QCCAC was lower than the respiratory function exercise care group (P < 0.05 ). After continuous nursing, the QCCAC's D-lactic acid, DAO, FFMI, Hb, ALB, PA, and other nutritional evaluation indexes all increased, and the QCCAC was significantly higher than the respiratory function exercise care group (P < 0.05 ). Conclusion . Quality control circle activity nursing combined with respiratory function exercise nursing can effectively improve the immune function, respiratory function, and nutritional status of esophageal cancer patients.